2020
DOI: 10.3389/fphys.2020.00139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spatiotemporal Urine Protein Dynamics to Identify New Biomarkers for Sepsis-Induced Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a frequent complication of sepsis and contributes to increased mortality. Discovery of reliable biomarkers could enable identification of individuals with high AKI risk as well as early AKI detection and AKI progression monitoring. However, the current methods are insensitive and non-specific. This study aimed to identify new biomarkers through label-free mass spectrometry (MS) analysis of a sepsis model induced by cecal ligation and puncture (CLP). Urine samples were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thus, it appears that despite the limitations, plasma is the most relevant biological sample for the identification of early sepsis biomarkers ( 141 ). However, it is likely that the future of predicting the onset of AKI will entail the combination of multiple proteomics analyses of samples from urine, plasma (rather than serum), and tissue ( 142 ), because any alteration in the release of a given protein and the abundance of such a protein in a given environment could reflect a pathological state. For example, a study on the temporal profile of renal proteome changes induced by sepsis highlighted that ceruloplasmin (CR) and haptoglobin (Hp) are upregulated 90 min after the onset of sepsis.…”
Section: Mass Spectrometry Characterization Applied To Infectious Dis...mentioning
confidence: 99%
“…Thus, it appears that despite the limitations, plasma is the most relevant biological sample for the identification of early sepsis biomarkers ( 141 ). However, it is likely that the future of predicting the onset of AKI will entail the combination of multiple proteomics analyses of samples from urine, plasma (rather than serum), and tissue ( 142 ), because any alteration in the release of a given protein and the abundance of such a protein in a given environment could reflect a pathological state. For example, a study on the temporal profile of renal proteome changes induced by sepsis highlighted that ceruloplasmin (CR) and haptoglobin (Hp) are upregulated 90 min after the onset of sepsis.…”
Section: Mass Spectrometry Characterization Applied To Infectious Dis...mentioning
confidence: 99%
“…Exosomes are membrane vesicles found in many biological fluids (such as blood or urine) that transmit signals between cells [ 23 ]. In the urine, the number of exosomes and extracellular vesicles increases continuously between 6 and 48 hours after induction of sepsis, suggesting that they could be potentially involved in this pathology [ 24 ]. It has been shown that exosomes play a role in sepsis through the interaction of various compounds released by the septic condition on membrane receptors.…”
Section: Mass Spectrometry For the Identification Of Sepsis Biomarmentioning
confidence: 99%
“…Among these targets, the acidic nucleic protein deglycase DJ-1 (PARK7) and cadherin 16 (CDH16) were found in samples from both models. This study also showed that the diagnostic sensitivities and specificities of PARK7 and CDH16 were greater than that of neutrophil gelatinase-associated lipocalin (NGAL), which is currently used to diagnose AKI [ 24 ]. Thus, these two proteins could potentially be considered as early biomarkers of sepsis-induced AKI.…”
Section: Mass Spectrometry For the Identification Of Sepsis Biomarmentioning
confidence: 99%
“…Massspectrometry-based proteomic analysis has been being a powerful screeningtool for the early detection of renal function and cancer-related biomarkers.Thisanalysishas been successfully utilized to identify protein biomarkers from body uids [12][13][14]. Unlike blood samples, urinecould be collected non-invasively and timely, moreover, urinecould better re ect the changes in the human body.Besides, the protein compositions of urinesamples are relatively simple, stable,and easier to analysis [15].…”
Section: Introductionmentioning
confidence: 99%